ULTRASOUND VERSUS MAGNETIC RESONANCE CHOLANGIO-PANCREATOGRAPHY IN THE DIAGNOSIS OF SUSPECTED EXTRA-HEPATIC INTRINSIC BILIARY OBSTRUCTION (Iraqi Journal of Medical Sciences, 2016)
Background:Evaluation of obstructive jaundice is a common clinical problem.Objective:To compare diagnostic accuracy, sensitivity and specificity of ultrasound and Magnetic Resonance Cholangio-Pancreatography in the diagnosis of intrinsic obstructive biliary disease.Methods: One hundred and sixty patients with an obstructive jaundice for whom ultrasound (U/S), magnetic resonance imaging (MRI) and Magnetic Resonance Cholangio-Pancreatography (MRCP) were performed. The final diagnosis was confirmed by surgery, tissue biopsy and/or Endoscopic Retrograde Cholangio-Pancreatography (ERCP) in some cases.Results:Of the 164 patients, 102 (62.2%) were found to have choledocholithiasis, 42 patients (25.6%) with benign stenosis and 20 patients (12.2%) had cholangiocarcinomas. Regarding choledocholithiasis, U/S examination showed a diagnostic accuracy of 80.15% with sensitivity of 71.08% and a specificity of 95.83 %. Conversely, MRCP showed a diagnostic accuracy of 93.89%, sensitivity of 93.97% and a specificity of 93.75 %. Regarding benign stenosis: U/S showed a diagnostic accuracy of 78.62% with a sensitivity of 16.67 % and a specificity of 97.29%. The diagnostic accuracy of MRCP was 93.13%, with a sensitivity of 90% and a specificity of 94.05%. In malignant stenosis: of the 20 patients with cholangiocarcinomas, 6 were localized in the upper third or hilar biliary tract (Klatskin tumor), 4 in the mid third and 10 in the distal third of the common bile duct (CBD). The diagnostic accuracy of US in malignant stenosis was 93.13%, with a sensitivity of 61.12% and a specificity of 98.23%. For MRCP, the diagnostic accuracy in detecting malignant stenosis was 93.89%, with a sensitivity of 72.23% and specificity of 97.34%. In all cases, no difference was noticed when comparing US and MRCP.Conclusion: Lithiasis was the most common cause of extra-hepatic intrinsic biliary obstructions. U/S is considered the first choice option in the diagnostic imaging of obstructive disease. If laboratory and clinical findings are supported by U/S, ERCP is required for therapeutic purposes, or if necessary surgery is performed. Ultrasound is highly reliable for ruling out benign stenosis, though not for demonstrating their presence. MRCP is required only for staging of malignant stenosis, or if the suspicion posed by clinical and laboratory findings is not confirmed at U/S.Key words:Ultrasound, MRCP, extra-hepatic intrinsic biliary obstruction.
Keywords: Ultrasound; MRCP; extrahepatic intrinsic biliary obstruction